PRINSIP, ASAS DAN KAIDAH HUKUM WARIS ISLAM ADIL GENDER (Universitas Suryakancana, 2017)
Theoretically, the Islamic inheritance law can be seen from different point of view basedon its object of law related to the division of property that has more dimension on civillaw and more closely within muamalah Fiqh as the scope of the study and related tointerpersonal law. Based on the writer's point of view, it is closer to the muamalahstudy which opens the possibility of ijtihad so that, Islamic law can be adapted in everyperiod of time. The problem of inheritance division assumed the concept of 'tribalism'and Islam comes to deconstruct the